Autologous melanoma cell vaccine using monocyte-derived dendritic cells (NBS20/eltrapuldencel-T). (March 2016) - Javed, Asad; Sato, Shingo; Sato, Takami
Targeted therapy and immunotherapy have revolutionized the treatment of advanced melanoma. Despite recent advances, lack of long-term efficacy from targeted therapy and serious immune-related toxicity are major concerns. There is unmet need for 'durable' and 'safe' treatment options for advanced melanoma. Cancer vaccine therapy in melanoma has been investigated for many years with modest clinical efficacy. More recently, dendritic cell-based vaccine products have become available for clinical use and have been the focus of investigation. CLBS20 (NBS20/eltrapuldencel-T) is a novel dendritic cell-based vaccine product that has shown promising results in early phase trials in advanced melanoma. This cancer vaccine approach could play an important role in providing a sustainable survival benefit, targeting cancer cells themselves and avoiding off-target immune-related toxicity.